2022
DOI: 10.3390/jcm11051290
|View full text |Cite
|
Sign up to set email alerts
|

Improved Kidney Allograft Function after Early Conversion of Fast IR-Tac Metabolizers to LCP-Tac

Abstract: Fast tacrolimus (Tac) metabolism is associated with a more rapid decline of renal function after renal transplantation (RTx). Because the pharmacokinetics of LCP-Tac (LCPT) and immediate-release Tac (IR-Tac) differ, we hypothesized that switching from IR-Tac to LCPT in kidney transplant recipients would improve the estimated glomerular filtration rate (eGFR), particularly in fast metabolizers. For proof of concept, we performed a pilot study including RTx patients who received de novo immunosuppression with IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…We can make the hypothesis that the improvement of tremors and neurologic symptoms after switch to LCPT can be explained by the C 0 /D ratio improvement. Previous studies have already shown that switching to LCPT increased tacrolimus bioavailability, C/D ratio, and was associated with a noticeable recovery of renal function in fast metabolizers [22]. These results are consistent with previous reports using the MeltDose ® technology, which demonstrated an increased bioavailability of LCPT compared with twice-daily formulations of tacrolimus [12,14,16] and with PR-TAC [30].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We can make the hypothesis that the improvement of tremors and neurologic symptoms after switch to LCPT can be explained by the C 0 /D ratio improvement. Previous studies have already shown that switching to LCPT increased tacrolimus bioavailability, C/D ratio, and was associated with a noticeable recovery of renal function in fast metabolizers [22]. These results are consistent with previous reports using the MeltDose ® technology, which demonstrated an increased bioavailability of LCPT compared with twice-daily formulations of tacrolimus [12,14,16] and with PR-TAC [30].…”
Section: Discussionsupporting
confidence: 91%
“…We can make the hypothesis that the improvement of tremors and neurologic symptoms after switch to LCPT can be explained by the C 0 /D ratio improvement. Previous studies have already shown that switching to LCPT increased tacrolimus bioavailability, C/D ratio, and was associated with a noticeable recovery of renal function in fast metabolizers [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the tremor and also the nephrotoxicity of Tac is related with a certain degree to Cmax, LCP-Tac (with lower Cmax) might be beneficial in susceptible patients, especially rapid metabolizers ( 87 , 144 ). Using retrospective data, we observed that switching to LCP-Tac was associated with a noticeable recovery of renal function in fast metabolizers ( 145 ). In liver transplant recipients, improvement in renal function was observed 12 months after conversion from standard-release Tac (IR- or ER-Tac) to LCP-Tac ( 146 ).…”
Section: Factors Influencing Tac Pharmacokineticsmentioning
confidence: 99%